Controle postural de idosos vestibulopatas crônicos com e sem histórico de quedas submetidos à estimulação visual por realidade virtual - Gazzola, Juliana Maria [UNIFESP] (2010)
Static posturography may assist the assessment of postural control in elderly patients with chronic vestibular disorder. Aims: To assess the postual control of elderly patients with chronic vestibular disorder, with or without history of falls through the static porturography integrated to virtual reality; to compare clinicalfunctional aspects between the elderly patients with chronic vestibular disorders, with or without history of falls. Method: A quantitative analytical research was performed through a transversal clinical study. Male and female elderly patients were included in the study, distributed into: control group (CG) - without falls or vestibular complaints, and functionally active; and group of patients with chronic vestibular disorder - group 1 (G1) with patients without history of falls, and group 2 (G2) with patients with history of falls. The static posturography assessment was performed using the Balance Rehabilitation Unit® (BRU®) to measure the parameters of the center of pressure (COP): stability limit (SL), COP area and velocity of body sway (VBS), in ten sensorial conditions. The following tests were used: Chi-Square or Fisher, ANOVA and Bonferroni, α=0,05. Results: Sample was constituted by 117 elderly patients: 67.5% female, mean age of 72.99 years, 41 (35.0%) of CG, 40 (34.2%) of G1 and 36 (30.8%) of G2. Groups did not present difference regarding gender, age and height. The SL of the CG was higher when compared to G1 (p<0.05) and G2 (p<0.05). The COP area presented higher values for G1 in comparison to GC (p<0.05) on firm surface conditions (FS) and closed eyes (CE), and on FS and visual vestibular interaction (VVI) in the horizontal direction. The COP area in all conditions, and the VBS in the condition of FS and open eyes (OE), FS and CE, FS and optokinetic stimulation downward and upward, and FS and VVI in the horizontal direction presented higher values for G2 in comparison to GC (p<0.05). The COP area in the condition of FS and OE, FS and CE, foam surface and CE, FS and saccadic stimulation, FS and optokinetic stimulation to the left and upward, and FS and VVI in the horizontal direction, and the VBS in the condition of FS and OE, FS and CE presented higher values for G2 in comparison to G1 (p<0.05). Elderly patients from G2 presented greater association with rotatory and non-rotatory dizziness (p<0.05) in comparison to G1. Conclusions: Healthy elderly patients presented better SL than elderly patients with chronic vestibular disorder with or without falls. Healthy elderly patients presented an area of COP and VBS similar to those of elderly patients with chronic vestibular disorder without falls, and better results in comparison with those who presented falls. Elderly patients with chronic vestibular disorder without falls presented a similar SL, better area of COP and similar VBS in comparison with those who presented falls; postural control in elderly patients with chronic vestibular disorder with falls was worse than it was in healthy elderly and patients with chronic vestibular disorder without falls.